2014
DOI: 10.1371/journal.pone.0109305
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine-Mediated Neuroprotection and Neuritogenesis of Axotomised Retinal Ganglion Cells by Human Dental Pulp Stem Cells: Comparison with Human Bone Marrow and Adipose-Derived Mesenchymal Stem Cells

Abstract: We have investigated and compared the neurotrophic activity of human dental pulp stem cells (hDPSC), human bone marrow-derived mesenchymal stem cells (hBMSC) and human adipose-derived stem cells (hAMSC) on axotomised adult rat retinal ganglion cells (RGC) in vitro in order to evaluate their therapeutic potential for neurodegenerative conditions of RGC. Using the transwell system, RGC survival and length/number of neurites were quantified in coculture with stem cells in the presence or absence of specific Fc-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
210
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(227 citation statements)
references
References 41 publications
16
210
0
1
Order By: Relevance
“…These results support the hypothesis that MSCs can act in secondary events favoring neuronal survival and regeneration (Nakamura et al, 2003;Yune et al, 2003;Mead et al, 2014).…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…These results support the hypothesis that MSCs can act in secondary events favoring neuronal survival and regeneration (Nakamura et al, 2003;Yune et al, 2003;Mead et al, 2014).…”
Section: Introductionsupporting
confidence: 87%
“…Similarly, the reduced TGF-β expression observed at 21 days in the GMSC may also have decreased formation of the glial scar and stimulated the recovery of motor function in the present study. As observed in previous studies (Hawryluk et al, 2012;Mead et al, 2014), MSCs cannot produce or stimulate the synthesis of BDNF. However, some authors reported increased expression of BDNF in animals subjected to injury and treated with MSCs (Osaka et al, 2010;Zhou et al, 2013;Kingham et al, 2014).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…107 Various stem cells such as embryonic stem cells, [108][109][110] hematopoietic stem cells, [111][112][113] mesenchymal stem cells (MSCs), [114][115][116] induced pluripotent stem cells, 117,118 and EPC 119,120 have been shown to demonstrate the capability to regenerate into retinal neurons, 108,[110][111][112][113]117 retinal pigmented epithelium, 109,121,122 and improve blood vessels permeability 123 in both in vitro and in vivo studies. It is noteworthy that the transplanted cells will need to survive the harsh microenvironment before cell programming can occur for the replacement of damaged tissue.…”
Section: Future Directionsmentioning
confidence: 99%
“…Indeed, secretome of DT-MSCs contains elevated levels of BDNF, neurotrophin-3, GDNF, and NGF (Mead, Logan et al 2014). In addition, compared to BM-MSCs and AD-MSCs secretome, DT-MSCs secreted important growth factors and cytokines such as VEGF, RANTES, FLT-3, MCP-1, Fractalkine, and GM-CSF (Ahmed et al 2016).…”
Section: Dental Tissues-derived Mscsmentioning
confidence: 99%